Das masculinidades - Barbosa, Barbara Cristina Souza; Guedes, Daniel Silva; Corso, Mário; Ballesteros, Yan Ribeiro (Percurso, 2023)
Realização: Bruno Esposito, Camila Junqueira, Gisela Haddad, Ivy Semiguem e Lucas Simões Sessa.